A Computational Meshless Method for Solving Multivariable Integral Equations - E. Babolian (Journal of Sciences, Islamic Republic of Iran)
In this paper we use radial basis functions to solve multivariable integral equations. We use collocation method for implementation. Numerical experiments show the accuracy of the method.